Ecological mechanisms underlying aridity thresholds in global drylands - Berdugo, Miguel; Vidiella, Blai; Solé, Ricard V.; Maestre, Fernando T. (Functional ecology, 2022)
With ongoing climate change, the probability of crossing environmental thresholds promoting abrupt changes in ecosystem structure and functioning is higher than ever. In drylands (areas where it rains <65% of what could be potentially evaporated), recent research has shown how the crossing of three aridity thresholds [at aridity (1‐Aridity Index) values of 0.54, 0.70 and 0.80] leads to abrupt changes on ecosystem structural and functional attributes. Despite the importance of these findings and their implications to develop effective monitoring and adaptation actions to combat climate change and desertification, we lack a proper understanding of the mechanisms unleashing these abrupt shifts. Here we review multiple mechanisms that may explain the existence of aridity thresholds observed across global drylands, and discuss the potential amplification mechanisms that may underpin hypothetical abrupt temporal shifts with climate change. We propose that each aridity threshold is caused by different and specific mechanisms. The first threshold is mainly caused by physiological mechanisms of plant adaptation to water shortages. The second threshold is unleashed by different mechanisms involving soil processes and plant–soil interactions such as soil erosion, plant community shifts and nutrient cycling and circulation. The collapse of vegetation observed once the third aridity threshold (0.8) is crossed is caused by the mechanisms related to the survival limits of plants that may cause sudden cover and diversity losses and plant–atmospheric feedbacks that link vegetation collapse with further climate aridification. By identifying, revising and linking relevant mechanisms to each aridity threshold observed, we provide a set of specific hypotheses and identify knowledge gaps concerning the study of threshold emergence in drylands. We were also able to establish plausible factors that are context dependent and may influence the occurrence of abrupt ecosystem changes in time. Our review may help to focus future research efforts on aridity thresholds and to develop strategies to monitor, adapt to or even revert abrupt ecosystem changes across global drylands. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.